«Der Konjunktiv hat sein Hauptlager in Österreich aufgestellt». Echi austriaci nella raccolta “die alarmbereiten” di Kathrin Röggla: [«The subjunctive has set up its main camp in Austria». Austrian echoes in the collection “die alarmbereiten” by Kathrin Röggla] (Studia austriaca, 2021)
The aim of this paper is to investigate the influence of Austrian Sprachskepsis on the poetics of the contemporary writer Kathrin Röggla, focusing especially on the use of the subjunctive as a legacy of the poet Ernst Jandl. The comparison between his poem Aus der Fremde – Sprechoper in 7 Szenen (1980) and die alarmbereiten (2010), one of Röggla’s most recent works, emphasizes how Röggla consciously continues the Austrian tradition that sees in Sprachkritik a fundamental tool of social criticism.